Triaxial compression testing on early age concrete for numerical analysis of 3D concrete printing - Wolfs, R.J.M.; Bos, F.P.; Salet, T.A.M. (Cement & concrete composites, 2019)
In 3D concrete printing processes, two competing modes of failure are distinguished: material failure by plastic yielding, and elastic buckling failure through local or global instability. Structural analysis may be performed to assess if, and how, an object may fail during printing. This requires input in the form of transient material properties obtained from experimental testing on early age concrete. In this study, a custom triaxial compression test setup was developed, to characterize all essential parameters to assess failure by elastic buckling, and material yielding according to the Mohr-Coulomb criterion. The results of the triaxial tests were compared to simultaneously run unconfined uniaxial compression tests and ultrasonic wave transmission tests. The correlation between these experimental methods was reviewed. It was concluded that the triaxial compression test is an appropriate method to determine all relevant transient properties from one series of experiments. Subsequently, the experimental results were used for structural analyses of straight printed walls of different lengths with a Finite Element Modelling approach. These walls have been printed up to failure during print trials and the results were compared to the numerical predictions. The failure mode is predicted accurately by the numerical model, as is the critical height at which failure occurs for relatively small objects. For larger objects and/or longer printing processes, the quantitative agreement of the critical height with the print experiments could be improved. Two possible causes for this deviation are discussed.